The Dynamic Impact of Intellectual Capital and Good Corporate Governance on Firm Value: Evidence from Indonesia - Adibah Yahya; Taufik Hidayat; Rina Nurjanah; Nando Dada Pratama (Cita Konsultindo Research Center, 2023)
Value investor perception of the company is often associated with the company's stock price, the higher the stock price will make the company's value is also high. The company's value becomes important, because the company's value reflects the return on investment of the investors. Investors will be very happy if get a higher rate of return on investment over time. The higher the value of the company, investors are increasingly interested in investing in these companies, so when the company needs funds for development of the company, investors will respond positively to invest capital to the company. The purpose of this research is to find out the influence of intellectual capital and good corporate governance to the firm value. The independent variables are intellectual capital and good corporate governance. Good corporate governance in this research is measured by indicators which consist of managerial ownership, institutional ownership, the board of directors, independent commissioners and audit committees. The dependent variables is the firm value which is measured by Tobins’Q. Data analysis method in this research is multiple linear regressions analysis with the SPSS 25th version application. The results showed that independent commissioners had a positive effect on firm value while the variables of intellectual capital, management ownweship, institutional ownweship, board of directors and audit committee had no effect on firm value.